NusA interaction with the α-subunit of E. coli RNA Polymerase is via the UP-element site and releases autoinhibition - Schweimer, Kristian (2011)
Elongating E. coli RNAP is modulated by NusA protein. The C-terminal domain (CTD) of the RNAP α-subunit (αCTD) interacts with the acidic CTD 2 (AR2) of NusA, releasing the autoinhibitory blockade of the NusA S1-KH1-KH2 motif and allowing NusA to bind nascent nut spacer RNA. We determined the solution conformation of the AR2:αCTD complex. The αCTD residues that interface with AR2 are identical to those that recognize UP promoter elements A nusA-ΔAR2 mutation does not affect UP-dependent rrnH transcription initiation in vivo. Instead, the mutation inhibits Rho-dependent transcription termination at phage λ tR1, which lies adjacent to the λ nutR sequence. The Rho-dependent λ timm terminator, which is not preceded by a λ nut sequence, is fully functional. We propose that constitutive binding of NusA-ΔAR2 to λ nutR occludes Rho. In addition, the mutation confers a dominant defect in exiting stationary phase.